Komunikasi Humanis dan Termanifestasikan Yang Berkeadaban Patrioteisme Kebangsaan Untuk Tatanan Beragama Yang Tatanan Sosial Berkeadaban Demokrasi - Zike Marta (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Guidance for democracy and national patriotism, both political and social, has become a universal agenda among the components of civil society (Civil Society), almost all parts of the world cannot be separated from the global guidance of this democracy, including Indonesia. In everyday political and social life, social behavior and political practice of the community are still often carried out with actions that are far from the noble values of Pancasila and democracy. Democracy which is a commitment of the reform movement is still filled with a culture of corruption and collusion committed by the community and officials. They want to be formal leaders and leaders of community and professional organizations. According to the author, the values of the principles of democracy can actually be practiced through the study of humanist democracy in higher education courses which are expected to be a laboratory to implement democratic principles that are integrated with the principles and values of universal democracy with the values of Pancasila